Water Wetting Observation on a Superhydrophobic Hairy Plant Leaf Using Environmental Scanning Electron Microscopy - Sun Mi Yoon; Tae-Jun Ko; Kyu Hwan Oh; Sahn Nahm; Myoung-Woon Moon (한국현미경학회, 2016)
Functional surfaces in nature have been continuously observed because of their ability to adapt to the environment. To this end, methods such as scanning electron microscopy (SEM) have been widely used, and their wetting functions have been characterized via environmental SEM. We investigated the superhydrophobic hairy leaves of Pelargonium tomentosum, i.e., peppermint-scented geranium. Their surface features and wettability were studied at multiple-scales, i.e., macro-, micro-, and sub-micro scales. The surfaces of the investigated leaves showed superhydrophobicity at the macro-, and micro-scales. The wetting or condensing behavior was studied for molecule-size water vapors, which easily adhered to the hairy surface owing to their significantly lower size in comparison to that of the surface.